2003
DOI: 10.1002/pssb.200301605
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic pressure dependence of recombination mechanisms in GaInNAs, InGaAsP and AlGaInAs 1.3 μm quantum well lasers

Abstract: From measurements of the threshold current and lasing energy as a function of pressure in InGaAsP/InP, AlGaInAs/InP and GaInNAs/GaAs based multiple quantum well lasers we determine the relative importance of the monomolecular, radiative and Auger recombination processes. For the InP based devices, we find that a simple combination of radiative and non-radiative Auger recombination can fully explain the pressure dependence of the threshold current where the threshold carrier density is approximately constant as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…Also shown is the pressure dependence of the radiative current, as determined from the integrated spontaneous emission at threshold (squares). The measured increase in I rad is in reasonable agreement with the ideal QW transparency model where I rad ∝ E g 2 dependence (dash-dot-dot line) [9], where E g is the band gap which is assumed to be equal to the measured lasing energy. However, the pressure dependence of the threshold current is stronger, particularly above 6 kbar.…”
Section: Pressure Dependencesupporting
confidence: 57%
See 2 more Smart Citations
“…Also shown is the pressure dependence of the radiative current, as determined from the integrated spontaneous emission at threshold (squares). The measured increase in I rad is in reasonable agreement with the ideal QW transparency model where I rad ∝ E g 2 dependence (dash-dot-dot line) [9], where E g is the band gap which is assumed to be equal to the measured lasing energy. However, the pressure dependence of the threshold current is stronger, particularly above 6 kbar.…”
Section: Pressure Dependencesupporting
confidence: 57%
“…The lower rate of increase of I th with pressure dependence compared to the leakage paths may be explained if carrier leakage together with a non-radiative process that decreases with pressure are both present. Auger recombination decreases with increasing pressure and is known to be important in other lasers operating over this wavelength range [9]. We therefore suggest that the non-radiative recombination which dominates I th at room temperature is due to a combination of carrier leakage and Auger recombination.…”
Section: T=300kmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, our results suggest the conclusion of Fehse et al that the band-to-band AR is not the dominant recombination process in N-based lasers. The measured change in normalized threshold current with pressure for the three competing laser devices by Sweeney et al [59] has shown that the threshold current of P-based lasers decreases with pressure whereas the threshold current of the other two increases with pressure, with rapid increments observed for N-based lasers. They have attributed this strong increase with pressure to the increase in n th with increasing pressure as a result of the heavier CB effective mass.…”
Section: Pressure Dependence Of Threshold Currentmentioning
confidence: 99%